Internationalization project cocktail team in-depth analysis of Spain - Zsigmond, Bence Pál (2023)
The aim of this paper is to analyze the internationalization opportunities for Cocktail Team, a Portuguese firm operating in the bar consulting industry. With this in mind an analysis of the Portuguese market for this sector was conducted as well as a firm analysis to assess their current situation and readiness for the project. Furthermore, multiple countries were analyzed, and four in-depth analyses were conducted resulting in the UK being chosen as the target market with the creation of an entry plan, involving a marketing and financial plan. The literature reviews and the the county analyses were conducted individually, while the rest of the paper were written as a group project by Miguel Sousa, Fernando Ribeiro, Gustavo Caneira and Bence Zsigmond. The individual contributions of my colleagues are not presented in this paper.